2003
DOI: 10.1074/jbc.m307154200
|View full text |Cite
|
Sign up to set email alerts
|

Trans-repression of β-Catenin Activity by Nuclear Receptors

Abstract: The signaling/oncogenic activity of ␤-catenin can be repressed by the activation of nuclear receptors such as the vitamin A, vitamin D, and androgen receptors. Although these receptors directly interact with ␤-catenin and can sequester it away from its transcription factor partner T-cell factor, it is not known if this is the mechanism of trans-repression. Using several different promoter constructs and nuclear receptors and mammalian two-hybrid and mutation analyses we now show that interaction with the co-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
89
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 36 publications
9
89
0
1
Order By: Relevance
“…[25][26][27] But, most studies reported that nuclear receptors repressed β-catenin signaling in the presence of ligand or agonist. 16,17,23,24 However, our data in the first time demonstrated that RXRα overexpression directly inhibited endogenous and exogenous β-catenin transcriptional activity and expression in the absence of RXR agonist. However, the inhibition was abrogated by targeted RXRα small RNA interfering.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…[25][26][27] But, most studies reported that nuclear receptors repressed β-catenin signaling in the presence of ligand or agonist. 16,17,23,24 However, our data in the first time demonstrated that RXRα overexpression directly inhibited endogenous and exogenous β-catenin transcriptional activity and expression in the absence of RXR agonist. However, the inhibition was abrogated by targeted RXRα small RNA interfering.…”
Section: Discussionmentioning
confidence: 59%
“…21,22 Recently, several lines of evidence showed that nuclear receptors affected β-catenin/TCF/LEF-mediated gene transcription and β-catenin protein. For example, retinoid-activated RAR acts as a potent repressor of β-catenin/TCF signaling in retinoid-sensitive colorectal cancer cells, 16,17,23,24 and activation of the vitamin D receptor with its metabolite ligand, 1α,25(OH) 2 vitamin D 3 , could repress Wnt/β-catenin/TCF signaling. [25][26][27] But, most studies reported that nuclear receptors repressed β-catenin signaling in the presence of ligand or agonist.…”
Section: Discussionmentioning
confidence: 99%
“…Western analysis was performed utilizing antibodies against ␤-catenin and actin. tors pathways (including vitamins A and D and androgen receptors) required the N-terminal 1-151 amino acids of ␤-catenin and involved the participation of the coactivator p300 (71). A similar mechanism might be activated following stimulation of PPAR␥, because the PPAR␥2-mediated pathway of ␤-catenin degradation also involved the N-terminal (1-131 amino acids) fragment of ␤-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…An active form of vitamin D, 1α,25-dihydroxyvitamin D3, and its synthetic derivatives have shown chemopreventive effects in animal models of colorectal and breast cancers. Although the mechanism by which vitamins inhibit Wnt/β-catenin signaling pathway is not fully understood, it is suggested that activated nuclear receptors for vitamins interact with β-catenin and compete with TCFs (70,71). Recently it has also been suggested that both vitamin A and D might induce Wnt/β-catenin inhibitory proteins, e.g., Disabled-2 (Dab2) by retinoic Polyphenols.…”
Section: Existing Drugs and Natural Compoundsmentioning
confidence: 99%